Survey of ICT and Education in Africa : Libya Country Report - Hamdy, Amr (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Libya boasts the highest literacy rate in the Arab world, and the United Nations (UN's) Human Development Index, which ranks standard of living, social security, health care and other factors for development, places Libya at the top of all African countries. Government reform plans in developing ICT infrastructure in Libya and incorporating ICT in education as key components in its overall development plans. Libya has intentions to be seen taking a leadership role on the African continent through sponsorship of major initiatives and projects, including those in the neighboring countries of Chad, Niger, and Rwanda. That said, the challenges of poor existing infrastructure and a lack of skilled and ICT-equipped teachers is a great challenge to the current reform process.